(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2024)
The percentage of teenagers aged ≥ 15 years who smoke in Central Java is ranked 10th with a percentage of 28.72 percent in 2023. The parenting style of parents with teenagers who smoke and youth youth activities are related. This research aims to look at parenting patterns, smoking and youth youth organization activities in Tanggeran Village. The sample consisted of 403 teenagers. The research used observational with a cross sectional approach. Data were collected using questionnaires on parenting patterns, teenage smoking, and youth organization activities. Data processing uses Descriptive Frequencies and Chi-Square tests. As for the results, parenting patterns show that 236 people (59.1%) are democratically involved, 304 people do not smoke (75.4%), and 166 people are less active (41.2%). For the relationship between parenting styles and teenagers’ smoking activities, there is a relationship where the p value = 0.000 ˂ α (0.05). Parental parenting styles influence teenagers’ smoking behavior and participating in activities outside the home such as youth groups. It is hoped that parents must actively guide and monitor the activities carried out by teenagers. Keywords: parenting patterns for teenagers smoking